2019
DOI: 10.1039/c9ce00245f
|View full text |Cite
|
Sign up to set email alerts
|

Controlled crystallization of anhydrous guanine β nano-platelets via an amorphous precursor

Abstract: We realized a pure phase of anhydrous guanine (AG) β form for the first time via a transformation from hydrated amorphous guanine phase (HAmG). The specified transformation was probably due to the similar short-range order between AG β and HAmG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 24 publications
3
62
0
Order By: Relevance
“…Considering that the a and b phase guanine crystalsa re very similar to each other and both form p-p stacking interactions between the neighborl ayers of the guanine molecules, it is reasonable that these polymer additives can absorba nd stabilize the (100) planes of both phases. [36] To the best of our knowledge,t his work represents the first study on the effects of guanine analogues with very similar molecular structure of guanineo nt he crystallization process of guanine,w here we found both morphology and crystallography can be tailoredw ith different types of guanine analogues. This study was inspired by the fact that ap articular guanine analogue, hypoxanthine,h as been previous identified as the second mosti mportant constituent in biological guanine crystals.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…Considering that the a and b phase guanine crystalsa re very similar to each other and both form p-p stacking interactions between the neighborl ayers of the guanine molecules, it is reasonable that these polymer additives can absorba nd stabilize the (100) planes of both phases. [36] To the best of our knowledge,t his work represents the first study on the effects of guanine analogues with very similar molecular structure of guanineo nt he crystallization process of guanine,w here we found both morphology and crystallography can be tailoredw ith different types of guanine analogues. This study was inspired by the fact that ap articular guanine analogue, hypoxanthine,h as been previous identified as the second mosti mportant constituent in biological guanine crystals.…”
mentioning
confidence: 66%
“…An umber of previouss tudies aimed to achieve similarc ontrol of the polymorph and morphology of guanine crystalssyntheticallyi nt he last years. [34][35][36][37][38] Utilizing chitosans ubstrates in the presence of poly(l-glutamic acid), Oaki et al synthesized a thin layer of aggregates of platy AG crystals,w hile it is unclear whether the synthesized AG is a or b phased ue to the low quality of X-ray diffraction patterns. [35] Gur et al demonstrated the polymorph controlb etween GM and AG by controlling the pH in the aqueous environment.…”
mentioning
confidence: 99%
See 3 more Smart Citations